The creation of scientific effects : Heinrich Hertz and electric waves - Buchwald, Jed Z. (University of Chicago Press, 1994)
This book is an attempt to reconstitute the tacit knowledge--the shared, unwritten assumptions, values, and understandings--that shapes the work of science. Jed Z. Buchwald uses as his focus the social and intellectual world of nineteenth-century German physics. Drawing on the lab notes, published papers, and unpublished manuscripts of Heinrich Hertz, Buchwald recreates Hertz's 1887 invention of a device that produced electromagnetic waves in wires. The invention itself was serendipitous and the device was quickly transformed, but Hertz's early experiments led to major innovations in electrodyna.